2012
DOI: 10.1115/1.4007096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Voxelized Model Based on DCE-MRI for Tracer Transport in Tumor

Abstract: Recent advances in the treatment of cancer involving therapeutic agents have shown promising results. However, treatment efficacy can be limited due to inadequate and uneven uptake in solid tumors, thereby making the prediction of drug transport important for developing effective therapeutic strategies. In this study, a patient-specific computational porous media model (voxelized model) was developed for predicting the interstitial flow field and distribution of a systemically delivered magnetic resonance (MR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…CED created additional pressure gradients (≈0.65 kPa/mm along the infusion plane) around the infusion site which were absent with systemic delivery. There was also significant pressure gradients at the anterior edge of the tumor-host tissue interface (≈0.67 kPa/mm) which was also observed without CED [32]. It should be noted that the pressure gradient outside the skin does not contribute to the extracellular fluid flow due to the very low hydraulic conductivity assigned in those voxels.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…CED created additional pressure gradients (≈0.65 kPa/mm along the infusion plane) around the infusion site which were absent with systemic delivery. There was also significant pressure gradients at the anterior edge of the tumor-host tissue interface (≈0.67 kPa/mm) which was also observed without CED [32]. It should be noted that the pressure gradient outside the skin does not contribute to the extracellular fluid flow due to the very low hydraulic conductivity assigned in those voxels.…”
Section: Resultsmentioning
confidence: 77%
“…The predicted velocity field was heterogeneous with maximum velocity near the infusion site (35 µm/s). There were also significant outwardly-directed flows at the tumor-host tissue interface especially near the anterior end of the tumor (≈0.45–3.2 µm/s) which was also observed with systemic delivery [32]. Thus CED has resulted in alterations of endogenous flows closer to the infusion site to a far larger magnitude.…”
Section: Resultsmentioning
confidence: 78%
“…Zhan et al modeled human liver tumor vasculature and concluded that not only drug accumulates faster in well vascularized regions but also clears out from these regions quickly, facilitating less tumor cell killing [11]. Attempts have also been made to model the heterogeneous vasculature of tumor tissues [12]. However, most of the studies had certain assumptions such as use of homogeneous model of tumors, use of global intravascular concentration or arterial input function (AIF), and heterogeneous models developed for animals with use of simple tofts kinetic model [13].…”
Section: Introductionmentioning
confidence: 99%
“…Sarntinoranont and coworkers have studied delivery of gadolinium diethylenetriaminepentaacetic acid (Gd-DTPA) delivery to brain tumors [30], and they calculate concentration of the Gd-DTPA using a method validated in an agarose phantom [31]. Sarntinoranont et al's studies seem to accurately calculate concentration with good spatial resolution; however, in our attempts to utilize a similar method for a different area of the body, additional studies into the potential sources of error and methods to minimize and quantify that error are warranted.…”
Section: Introductionmentioning
confidence: 99%